2015
DOI: 10.1155/2015/324843
|View full text |Cite
|
Sign up to set email alerts
|

Iron Accumulation Is Not Homogenous among Patients with Parkinson’s Disease

Abstract: Background. Iron is considered to lead to neurodegeneration and has been hypothesized as a possible cause of Parkinson's disease (PD). Susceptibility-weighted imaging (SWI) is a powerful tool to measure phase related iron content of brain. Methods. Twelve de novo patients with PD were recruited from the Movement Disorders Clinic, Department of Neurology, Loma Linda University. Twelve age- and sex-matched non-PD subjects were recruited from neurology clinic as controls. Using SWI, the phase related iron content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
3
28
0
3
Order By: Relevance
“…17,18 A heterogeneous iron content was noted across PD patients, despite the homogeneity of their unilateral bradykinesia, and rigidity. 19 The combination of SWI and R2* has shown enhanced relaxation and susceptibility in the SNc and anterior GP in PD with R2*, but not SWI, values correlating with tremor and disease duration. 20 Nigrosomes are small clusters of dopaminergic cells within the SN exhibiting calbindin D28K negativity on immunohistochemical staining.…”
Section: Substantia Nigramentioning
confidence: 91%
See 1 more Smart Citation
“…17,18 A heterogeneous iron content was noted across PD patients, despite the homogeneity of their unilateral bradykinesia, and rigidity. 19 The combination of SWI and R2* has shown enhanced relaxation and susceptibility in the SNc and anterior GP in PD with R2*, but not SWI, values correlating with tremor and disease duration. 20 Nigrosomes are small clusters of dopaminergic cells within the SN exhibiting calbindin D28K negativity on immunohistochemical staining.…”
Section: Substantia Nigramentioning
confidence: 91%
“…Lower levels of phase radians in the SNc as well as in the caudate nuclei and RN, with higher phase shift in SNc and basal ganglia (BG), were found in PD patients, implying an increased iron content correlating with UPDRS scores . A heterogeneous iron content was noted across PD patients, despite the homogeneity of their unilateral bradykinesia, and rigidity . The combination of SWI and R2* has shown enhanced relaxation and susceptibility in the SNc and anterior GP in PD with R2*, but not SWI, values correlating with tremor and disease duration …”
Section: Structural Imagingmentioning
confidence: 99%
“…A possible explanation of this finding may be that consecutive gliosis with neuronal degeneration in late‐stage PD might lengthen T2 relaxation times within the tissue and thus counteract the increase of relaxation rates . This could also explain that some authors found no difference in iron content between PD patients and HCs, whereas most studies did . Although relaxometry might track disease progression early in the disease process, available evidence suggests that relaxometry may not be a sufficient staging biomarker by itself .…”
Section: High‐field Mri Of Parkinsonism and Its Progressionmentioning
confidence: 99%
“…Nigral changes reflecting increases have been consistently reported in PD at 1.5T and 3T . However, PD values overlapped with those of HCs, and a few studies found no changes in PD, limiting its clinical use as disease marker today . Increased iron content was also reported in symptomatic and asymptomatic leucine‐rich repeat kinase 2 ( LRRK2 ) and Parkin mutation carriers .…”
Section: High‐field Mri Of Parkinsonism and Its Progressionmentioning
confidence: 99%
See 1 more Smart Citation